Thriving in the New Normal: The HR Microfoundations of Capabilities for Business Model Innovation. An Integrated Literature Review. (26th February 2020) - Loon, Mark; Otaye‐Ebede, Lilian; Stewart, Jim
Abstract: Firms need to respond to the increasing competition and change of the current New Normal environment by being more innovative, and especially in developing new business models. This paper seeks to explore how microfoundations, particularly with respect to human resource management, play a key role in facilitating innovation in business models through the development of key needed capabilities. Four themes are identified with respect to business model innovation (BMI) in the New Normal: BMI as an enabler to create and operate across industries and product‐markets; BMI as a mechanism for firms to better navigate changing institutional landscapes; BMI as giving rise to business model portfolios; and concurrent and cumulative innovations that can lead to BMI. This paper also develops a conceptual framework that presents a synoptic view of the five essential capabilities for BMI, which include analogical reasoning, sensemaking, dynamic capabilities, organisational ambidexterity, and organisational learning. Finally, it is shown how the microfoundations of a bespoke, development‐oriented BMI HR architecture can support the advancement of these capabilities and thus contribute to the strategic HR literature.